Affinities or Apparent Affinities of the Transport Adenosine Triphosphatase System - Glynn, I. M. (The Rockefeller University Press, 1969)
The interactions of potassium ions and ATP on transport ATPase activity are discussed, and the interpretation of these interactions is shown to be often ambiguous. Caldwell's (1968) Physiological Review model is discussed with particular reference to the observed kinetics of sodium: sodium exchange in red cells. Recent experimental work on the properties of the ouabain-sensitive component of potassium efflux from red cells is described. This component of efflux occurs only if either sodium or potassium are present in the external medium, but the effects of external sodium and potassium are not additive. The relation between ouabain-sensitive potassium efflux and the external concentration of sodium (in a potassium-free medium) or of potassium (in low- and high-sodium media) are described. When starved sodium-poor red cells are poisoned with iodoacetamide, loaded with phosphate, and incubated in high-sodium potassium-free media, the ouabain-sensitive efflux of potassium appears to be accompanied by the reversal of the entire ATPase system. About two to three potassium ions leave by the ouabain-sensitive route for each molecule of ATP synthesized. If potassium is present in the external medium, no ouabain-sensitive synthesis of ATP occurs and the ouabain-sensitive efflux of potassium presumably involves the reversal of only the last part of the ATPase system.